ANALYSIS OF OPAC SATISFACTION LEVEL IN POLITEKNIK KESELAMATAN TRANSPORTASI JALAN LIBRARY WITH PIECES FRAMEWORK - Ikapraja, Bagus; Siswanto, Joko (ITP Press, 2024)
OPAC has a significant effect on the quality of user service satisfaction, both partially and simultaneously. The problems with OPAC in higher education libraries are that information on book locations is not appropriate, information on book availability is less valid, lack of knowledge, lack of computer facilities, and barriers to access to information. The OPAC SliMS satisfaction analysis of the Tegal Road Transportation Safety Polytechnic Library is proposed with 4 research stages consisting of the identification stage, indicator development, data analysis, results and findings. PIECES (Performance, Information, Economy, Control, Efficiency and Service Framework) was adopted to compile indicators and analyze the level of satisfaction of 263 respondents. Data analysis is based on 30 questions in the questionnaire given to respondents in January 2023. The results of the analysis show that efficiency has a level of satisfaction was the highest with a score of 4.10 which was in the very satisfied category, while performance had the lowest level of satisfaction with a score of 3.96 which was in the satisfied category. These results can be used as a reference for making improvements to improve the quality of library services from the perspective of user satisfaction of the SLiMS OPAC application.